Complications of urethral surgery - B. R. Gvasalia; M. U. Babaev; A. V. Isaeva; A. B. Bogdanov; Yu. P. Gorobets; D. A. Chesnov (Вестник урологии, 2025)
Reconstructive urology encompasses a diverse array of surgical modalities for the management of urethral strictures in the male population. Despite the extensive documentation of various surgical approaches and their purported benefits in the existing literature, there remains a notable paucity of comprehensive data regarding intraoperative and postoperative complications. These adverse events unequivocally exert a significant impact on patients’ quality of life and overall treatment satisfaction. The present manuscript provides a systematic review of the international literature pertaining to potential complications associated with diverse therapeutic interventions for urethral stricture disease.